An Algorithm for Free Clinic Deployment: Bridging the Gap in Healthcare Access in Rural Pennsylvania - Shayann Ramedani; Vladimir Khristov; Maryknoll Palisoc; Megan Mendez Miller (Journal of Student-Run Clinics, 2022)
Student-run free clinics play an essential role in meeting the needs of underserved populations while providing service-learning opportunities to health professions students. While these clinics have been an asset for many institutions, the success hinges on the successful selection of clinic locations, studying resource utilization, the receptiveness of the local population, and effective strategic planning. The Student-led and Collaborative Outreach Program for Health Equity (SCOPE) Free Mobile Clinic at the Pennsylvania State University College of Medicine was established in 2017 to address the needs of underserved populations in Central Pennsylvania. Starting from one clinic, SCOPE has grown to twelve different sites across the county and has addressed different needs in diverse populations from rural to urban. The clinic has reached 435 individuals, provided 95 consultations with attending physicians, and distributed more than 120 vaccinations in the three years it has been fully active. During its evolution, the organization has developed a guidance algorithm that is critical to its operations and expansion initiatives. This algorithm has enabled strategic community resource deployment, garnered interest from private nonprofit collaboration and local government investment. Based on objective data, we identified new patient populations and clinic sites. Here we describe our experience developing and utilizing our deployment algorithm and the challenges and lessons we learned in growing a novel clinic model in a rural landscape.